2017
DOI: 10.1097/rhu.0000000000000466
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Treatment of Latent Tuberculosis Among Patients Receiving Biologic Agents

Abstract: There is a large disagreement regarding the method used and how often to screen for LTBI after initiating biologic therapy and how soon biologic treatment would be started after initiating LTBI therapy. Another disagreement exists regarding the duration of LTBI therapy. The information obtained from the survey can be taken into account when ACR or other international member organizations formulate future recommendations regarding screening and treatment of LTBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“… 50 Nevertheless, even in low TB prevalence countries, the majority of rheumatologists are still employing such retesting strategies. 52 In a recent study in a low prevalence country such as Greece, we found that conversion of screening assays (TST, IGRA) during long-term bDMARD therapy was common and in most cases a transient event. 53 Similarly, high conversion rates of IGRAs have been reported in health care workers during routine annual re-screenings and thus, the Centre for Disease Control (CDC) does not recommend them universally anymore, except for those at increased TB risk.…”
Section: Opportunistic Infectionsmentioning
confidence: 91%
“… 50 Nevertheless, even in low TB prevalence countries, the majority of rheumatologists are still employing such retesting strategies. 52 In a recent study in a low prevalence country such as Greece, we found that conversion of screening assays (TST, IGRA) during long-term bDMARD therapy was common and in most cases a transient event. 53 Similarly, high conversion rates of IGRAs have been reported in health care workers during routine annual re-screenings and thus, the Centre for Disease Control (CDC) does not recommend them universally anymore, except for those at increased TB risk.…”
Section: Opportunistic Infectionsmentioning
confidence: 91%
“…They also differed on the frequency of LTB screening after initiating biologic therapy and the time of initiation of biologic treatment after starting LTBI therapy. Moreover, there is no consensus on the duration of LTBI therapy . The British Thoracic Society recommends collecting the details of TB risk factors and performing a CXR.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies were rated to have a low risk of bias ( n = 35) 10 , 17–27 , 29 , 31 , 33–35 , 38 , 39 , 41–44 , 46 , 47 , 49–54 , 56 , 60–62 , and 12 studies had a moderate level of risk of bias 28 , 30 , 32 , 36 , 37 , 40 , 45 , 48 , 55 , 57–59 ( Supplementary Appendix 7 ). The risk of bias primarily arose from a lack of reporting on the sampling frame ( n = 28) 10 , 17 , 28–30 , 32–34 , 37 , 38 , 40 , 41 , 43–48 , 50 , 52–55 , 57–59 , 61 , 62 and the sampling method where convenience sampling or voluntary sample was used ( n = 20). 17 , 21 , 22 , 27 , 29–31 , 33 , 36 , 38 , 42–44 , 46 , 47 , 49 , 50 , 52 , 56 , 58 Hence, there was uncertainty on whether the true close representation of the target population was established.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, half of the studies ( n = 23) did not use pilot-tested and validated study instruments for data collection. 20 , 21 , 23 , 25 , 26 , 30 , 32–38 , 41 , 47–49 , 52 , 55 , 57 , 61 , 62 This could potentially affect the reliability, consistency and accuracy of data collected.…”
Section: Resultsmentioning
confidence: 99%